Strengthening Superior Tourist Village Governance Administration: Perspectives from Human Resources, Public Services, and Social Media - Emil Al-Fath Ilmawan; Mulyaningsih; Aceng Ulumudin; Benni Yandiana (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Indonesia’s tourist villages are expanding, yet many “superior” villages struggle to translate growth into accountable and sustainable governance. This study synthesizes evidence on how human resources, public services, and social media strengthen village-level tourism administration. Drawing on sustainable tourism governance, collaborative governance, and smart tourism perspectives, we conducted a PRISMA 2020–guided systematic literature review of Scopus Q1 journals (2015–2026). From 80 screened records, 30 articles met eligibility and were analyzed through iterative thematic coding. Results indicate governance improves when (1) HR capacity building embeds sustainability and digital competencies, (2) public services are digitized to standardize processes, enhance transparency, and improve service quality, and (3) social media is managed as participatory feedback and branding infrastructure. Yet digital divides and resource constraints may erode gains unless policy instruments and cross-sector partnerships provide enabling support. We propose an integrated three-step governance model aligned with ESG, emphasizing social and governance dimensions for rural destinations. Keywords: Public Service Digitalization, Social Media Governance, Tourist Village Governance